Estimating excess mortality due to female genital mutilation - Arpita Ghosh; Heather Flowe; James Rockey (Scientific Reports, 2023)
Abstract Globally, over 200 million women and girls have been subjected to Female Genital Mutilation (FGM). This practice, illegal in most countries, often happens in unsanitary conditions and without clinical supervision with consequent bleeding and infection. However, little is known about its contribution to the global epidemiology of child mortality. We matched data on the proportion of girls of a given age group subject to FGM to age-gender-year specific mortality rates during 1990–2020 in 15 countries where FGM is practised. We used fixed-effects regressions to separate the effect of FGM on mortality-rates from variation in mortality in that country in that year. Using our estimated effect, we calculated total annual excess mortality due to FGM. Our estimates imply that a 50% increase in the number of girls subject to FGM increases their 5-year mortality rate by 0.075 percentage point (95% CI $$0· 065$$ 0 · 065 – $$0· 085$$ 0 · 085 ). This increased mortality rate translates into an estimated 44,320 excess deaths per year across countries where FGM is practised. These estimates imply that FGM is a leading cause of the death of girls and young women in those countries where it is practised accounting for more deaths than any cause other than Enteric Infections, Respiratory Infections, or Malaria.